Factors Affecting the Proper Functioning of a 3Ah Li-S Pouch Cell. Issue 13 (1st January 2017) - Salihoglu, Omer; Demir-Cakan, Rezan
Abstract : The research on Li-S batteries is definitely progressing and superior cycling performances are achieved at the laboratory scale. Now the question is how all this great knowledge gained from the small laboratory scale experiments would be implemented into the large scale cells while still be able to outperform the Li-ion batteries readily available at the marketplace. Herein, every aspects of the manufacturing of a 3 Ah Li-S pouch cell are unveiled and discussed in details that are conclusively an undisclosed process. As expected, it is found that when the coin cell tests are adapted to the pouch cell, much pronounced problems are detected resulting much faster cell failure. Initially the pouch cell is exhibited 120 Wh/kg energy density based on the mass of the entire cell and losses its almost 85% capacity after 100 cycles. Experimentally speaking, relatively low gravimetric energy density and the short cycle life of the Li-S cells are directly linked with the lower sulfur utilization, unprotected Li metal anode as well as to the need to operate in excess of electrolyte which occupies more than 60 wt% of the entire cell imposing a great penalty in terms of energy density to the Li-S system.